Does low-level laser therapy decrease pain and edema in patients undergoing orthognathic surgery? Systematic review and meta-analysis - de Paula Ribeiro Borges, Danilo (2024)
Aim: This systematic review purposed to investigate whether low-level laser therapy is effective in reducing pain and edema in patients undergoing orthognathic surgery. Materials and Methods: An electronic search was conducted in PubMed, SCOPUS, Embase, SciELO, Web of Science, LILACS, IEEE XPLORE, Google Scholar, Open Thesis, OpenGrey, and Open Access Thesis and Dissertationswith no restrictions on language or year of publication. PICOS strategy wasused to define the eligibility criteria. The risk of bias (ROB 2.0 Tool) andmethodological quality assessment was carried out, and a meta-analysis was performed using a random-effect model. The quality of evidence was classified with the GRADE (Grades of Recommendation, Assessment, Development, and Evaluation) classification system. The analyses were performed with Review Manager 5.3 (Cochrane IMS, Copenhagen, Denmark). Results: A total of 1255 potentially relevant records were selected through the search strategy. After screening titles and abstracts, five full-text manuscripts were assessed for eligibility and three randomized controlled trials (RCTs) were included in the meta-analysis. Results favourable to low-level laser therapy were found both for the pain outcome (p < 0.0001) and edema (p = 0.001). Conclusion: Considering the limitations of this systematic review, low-level laser therapy showed a positive effect in reducing pain and edema in the postoperative period of bimaxillary orthognathic surgeries, with moderate and high-quality evidence, respectively.